Becoming Chinese with the Chinese: The Missionary Contribution of Matteo Ricci: Menjadi Tionghoa bersama Orang Tionghoa: Kontribusi Matteo Ricci dalam Evangelisasi - Duraj, Jaroslaw (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2024)
Matteo Ricci is one of the most important Christian missionaries in China whose groundbreaking method of accommodation in the context of the Chinese culture was paradigmatic and influenced the history of relationship between China and the West. Ricci’s work had a profound impact on Chinese culture. He introduced new ideas in astronomy, mathematics, cartography, and other fields. He also helped to spread Christianity in China through the means of science and dialogue built on authentic friendship. In this article we offer a discussion about his missionary work that left mark on the history of evangelization of China by considering his scientific contribution, his missionary spirituality and accommodation method resulting in his personal experience of intercultural encounter leading to his profound self-transformation. As the Catholic church already officially recognized his “heroic virtues” putting Matteo Ricci on the path to sainthood, it is important to reflect about contribution of this great Jesuit to the dialogue between China and the West. Abstrak Matteo Ricci adalah salah seorang misionaris Kristen terpenting di Tiongkok, karena membuat terobosan berupa metode akomodasi yang akan menjadi paradigma kultural yang memengaruhi sejarah relasi antara Tiongkok dan Barat. Pengaruh Ricci terhadap kebudayaan Tiongkok sangat dalam karena ia memperkenalkan astronomi, matematika, kartografi, dan bidang ilmu lainnya. Ia membantu penyebaran Kristianitas di Tiongkok lewat jalan ilmu pengetahuan serta lewat dialog berdasarkan persahabatan tulus. Artikel ini mendiskusikan karya Ricci yang menandai sejarah evangelisasi di Tiongkok dengan secara khusus menyoroti kontribusinya dalam bidang sains dan dengan menelisik metode akomodasi beserta spiritualitas penginjilannya yang berakar pada perjumpaan interkultural yang membuahkan transformasi mendalam dalam kehidupan pribadinya. Mengingat Gereja Katolik telah secara resmi mengakui keutamaan-keutamaan heroik Matteo Ricci serta telah memulai proses kanonisasinya, penting kiranya merefleksikan kontribusi misionaris Yesuit ini dalam hal dialog antara Tiongkok dan Barat. Kata-kata kunci: Matteo Ricci, Tiongkok, spiritualitas, akomodasi, misi, dialog